Tooth decay detection using a fiber optic sensor - Benjumea-Mendoza, Eberto; Díaz, Leonardo; Torres, César (Revista Facultad de Odontología Universidad de Antioquia, 2018)
Introduction: tooth decay has become one of the most prevalent diseases worldwide, but ironically it is one of the most neglected. Currently, adequate and effective caries treatment is based on early diagnosis and procedures such as sealants, crowns, and root canal treatment. Methods: This study examined the behavior of carious and non-carious areas of critical dental units (premolars and molars) subjecting them to a wavelength of 830 nm in adult humans who agreed to a dental exam and had at least one tooth affected by dental caries. Underage persons and patients in medical treatment were excluded. After finding a behavior that helped differentiate decayed tissue from healthy areas, the used experimental system was characterized and tested in volunteers. The implemented system contains a fiber optic sensor comprised of a trifurcated fiber and a photodetector to perform optical power measurements. Results: This sensor detected 100% of dental caries samples on premolar and molar occlusal surfaces. It also showed the ability to diagnose buccal cavities. Conclusions: The results showed that caries can be identified in dental units by means of a fiber optic sensor and infrared light at 830 nm.